Paleoenvironmental changes of source rocks from the Carboniferous to Permian sediments of the Mahu Sag, Junggar Basin, China. Issue 5 (2nd September 2020) - Feng, Chong; Ma, Mingze; He, Wenjun; Li, Teng; Wu, Qiuyu; Zhang, Zexin; Zhao, Haiyang
ABSTRACT: There are four sets of source rocks from Carboniferous (C) to Permian in Mahu Sag, and the paleoenvironment is the decisive factor for the differences of source rocks. In order to study the controlling effect of paleoenvironmental evolution on the change of source rock properties, the major, trace elements and the total organic carbon (TOC) of 47 core samples from four sets of source rocks were tested. The results indicate that the paleoenvironmental evolution of these four sets of source rocks from C to Permian in Mahu Sag can be divided into five stages. At the end of C and the early stage of deposition of Wuerhe formation (P2 w), the paleo climate became warm and humid, and the salinity of water body became small. Meanwhile, the oxidizability of water body gradually became stronger. At the deposition stage of Jiamuhe Formation (P1 j), Fengcheng Formation (P1 f) and the late stage of deposition of P2 w, the paleo climate gradually became hot and dry, and the salinity of water body gradually increased. Meanwhile, the reducibility of water body became stronger. The paleoenvironmental factors controlling the abundance of organic matter in source rocks are different in different stages.